Non-parametric Identification of the Mixed Hazards Model with Interval-Censored Durations - Christian N. Brinch (Statistics Norway, Research Department, 2008)
Econometric duration data are typically interval-censored, that is, not directly observed, but observed to fall within a known interval. Known non-parametric identification results for duration models with unobserved heterogeneity rely crucially on exact observation of durations at a continuous scale. Here, it is established that the mixed hazards model is non-parametrically identified through covariates that vary over time within durations as well as between observations when durations are interval-censored. The results hold for the mixed proportional hazards model as a special case.
Keywords: C41; 330; duration analysis; interval-censoring; non-parametric identification